Exploration of Sustainability Literacy Through Environmental Perspectives in the Context of Energy Conservation and Transformation - Diantika Ayuningrum; Eko Hariono; Mita Anggaryani; Muhammad Satriawan; Binar Kurnia Prahani; Hanandita Veda Saphira (Universitas Pendidikan Mandalika, 2025)
Sustainability is a major challenge in the 21st century that must be managed by physics learning. This study aims to explore students' sustainability literacy in the context of energy conservation and transformation through physics questions created with an environmental approach. This study uniquely integrates local pesantren contexts into physics education to address sustainability literacy, offering a novel contribution to science education by incorporating cultural and contextual relevance. With a descriptive exploration of 30 grade X students from senior high school Nurul Jadid, the research was conducted using tests, questionnaires, and interviews. The results on the knowledge dimension showed that students performed very well at low cognitive levels, but higher-order thinking skills, especially evaluation and creation, were still low. In the skill dimension, students' ability to solve problems was moderate, with weaknesses in the aspects of evaluation and reflection. Although students responded well to the contextual problems, many had difficulty in drawing energy transformation schemes. These results indicate the need for more practical and contextualized learning to strengthen sustainability literacy in physics learning.